Incorporation of interference fit and cyclic loading in simulation algorithm for better prediction of micromotion of femoral stems - Abdul-Kadir, Mohammed Rafiq; Hansen, Ulrich N. (Penerbit UTM Press, 2007)
Aseptic loosening is one of the major causes for revision surgery in hip arthroplasty. This has been attributed to failure in achieving strong primary fixation. Interface micromotion beyond a certain threshold limit inhibits bone ingrowth and favours the formation of fibrous tissue. In this study, an algorithm was constructed to predict micromotion and therefore instability of femoral stems. Based on common physiological loading, micromotion is calculated throughout the bone-implant interface. Press fit stem insertion was modelled using interference fit and cyclic loading was used to better simulate actual loading configuration. An in-vitro micromotion experiment was carried out on four human cadaveric femurs to validate the micromotion algorithm. A good correlation was obtained between finite element predictions and the in-vitro micromotion experiment.